Produção de 2,3-Butanodiol a partir de glicerol por klebsiella oxytoca ATCC 8724 - Romio, Tiago (My University, 2015)
Glycerol is a by-product of biodiesel production, which accounts for approximately 10% of the biofuel. Since a large volume of it is formed in industry, glycerol could be used as a substrate to obtain other compounds, such as 2,3-butanediol, through fermentative routes. This substance, which has potential for application in industry and as fuel, can be obtained by glycerol fermentation with the facultative anaerobe bacterium Klebsiella oxytoca. In this work, parameters and operational conditions for the cultivation of K. oxytoca ATCC 8724, envisaging 2,3-butanediol production from glycerol, were assessed. Due to the equilibrium between 2,3-butanediol and acetoin, in a significantly higher proportion for the first product, in the fermentative metabolism of K. oxytoca, the discussion of this work takes in account the sum of concentrations of these compounds. The results have shown that the microorganism is able to efficiently metabolize glycerol once cell growth rate on this substrate, after 8 hours of cultivation in shake flasks, was 0.44 g/L/h, higher than that obtained with glucose (0.38 g/L/h) under the same conditions. As previously described for saccharides, it was observed that the microbial metabolism can be divided into two phases: in the first phase, without limitation of oxygen, an intense cell growth occurs due to the prevalence of respiration, that results in a substantial gain of energy for the microorganism, whereas in the second phase, under oxygen limitation, most of carbon flux is driven to the formation of fermentation products. Thus, in batch runs carried out in a bench bioreactor, the use of an intermediate characteristic oxygen transfer rate (OTR) of about 17 mmol/L/h, led to superior results in terms of 2,3-butanediol production, with conversion of 60 g/L of glycerol to 17.3 g/L of product. In batch mode, the highest conversion of glycerol to product was achieved with 129 g/L of initial substrate concentration, with the production of 53.6 g/L 2,3-butanediol, in 48 hours, which means a yield of 83% in relation to the theoretical maximum. With initial glycerol concentrations up to 60 g/L, no inhibitory effect on cell growth was observed. On the other hand, the use of 160 g/L of glycerol led to a drastic decrease in the process yield to 56.3% and to a residual concentration of substrate of 98 g/L after 72 h of cultivation. By carrying out the process in fed-batch mode, as an alternative to overcome the substrate inhibitory effects, remarkable results have been attained with the mass of glycerol that would be needed to have an initial concentration of 202 g/L in batch mode. Under these conditions, a final concentration of 92.1 g/L of 2,3-butanediol, corresponding to a yield of 92.6%, was achieved after 84 hours of fermentation. The results show clearly the high potential of the use of glycerol as a substrate for 2,3- butanediol production in industrial scale.
Glicerol é um álcool gerado na produção de biodiesel, que corresponde 10% em relação ao biocombustível. Devido à crescente produção de biodiesel, pode ser utilizado como substrato para a obtenção de outros compostos, como o 2,3-butanodiol, através de vias fermentativas. Esta substância, que tem potencial de aplicação industrial e como combustível, pode ser obtida pela fermentação de glicerol pela bactéria anaeróbia facultativa Klebsiella oxytoca. Neste trabalho foram avaliados parâmetros e condições operacionais para o cultivo de K. oxytoca ATCC 8724, visando à obtenção de 2,3- butanodiol a partir de glicerol. Em razão do equilíbrio observado entre 2,3-butanodiol e acetoína, em proporção significativamente maior para o primeiro, no metabolismo fermentativo de K. oxytoca, a discussão dos resultados deste trabalho levam em conta a soma das concentrações destes compostos. Os resultados indicaram que este microrganismo metaboliza eficientemente o glicerol, visto que a velocidade média de crescimento celular neste substrato, em 8 horas de cultivo em frascos sob agitação, foi de 0,44 g/L/h, superior à obtida com glicose (0,38 g/L/h) nas mesmas condições. Observou-se que para substratos sacaríneos, que o metabolismo microbiano pode ser dividido em duas fases: na primeira fase, sem limitação de oxigênio, ocorre acentuado crescimento celular, em razão da prevalência da respiração, que resulta em substancial ganho energético para o microrganismo, enquanto na segunda fase, com limitação de oxigênio dissolvido, o fluxo de carbono é cada vez mais dirigido à formação de produtos de fermentação. Assim, em ensaios em regime descontínuo conduzidos em biorreator de bancada, o uso de uma velocidade característica de transferência de oxigênio (OTR) intermediária, da ordem de 17 mmol/L/h, proporcionou resultados superiores em termos de produção de 2,3-butanodiol, com conversão de 60 g/L de glicerol em 17,3 g/L do produto. Em regime descontínuo, a mais alta conversão de glicerol em produto foi alcançada com concentração inicial de substrato de 129 g/L, sendo produzidos, em 48 horas, 53,6 g/L de 2,3-butanodiol, o que significa um rendimento superior a 83% em relação ao máximo teórico. Com concentrações iniciais de glicerol de até 60 g/L, não foi constatado efeito inibitório sobre o crescimento celular. Por outro lado, o uso de 160 g/L de glicerol inicial levou a uma drástica redução do rendimento do processo (apenas 56,3%) e a uma concentração residual de substrato de 98 g/L, após 72 de cultivo. Com a condução do processo em regime descontínuo alimentado, como alternativa para contornar os efeitos de inibição pelo substrato, resultados expressivos foram alcançados com a massa de glicerol equivalente à que seria necessária para ter-se 202 g/L em regime descontínuo. Nestas condições, 92,1 g/L de 2,3-butanodiol e rendimento de 92,6%, foram alcançados, em 84 horas de fermentação. Os resultados revelam, o grande potencial de uso de glicerol como substrato para a produção de 2,3-butanodiol em escala industrial.
Keywords: Biocombustíveis; Bactérias; Fermentação; Biomass energy; Bacteria; Fermentation